An analysis of the pre-service primary teacher education program in Afghanistan and recommendations for its improvement - Munsif, Mohammad Mohsin 1935- ([s.n.], 1972)
The purpose of the study is to analyze the existing primary teacher education program in Afghanistan in order to identify its strengths and weaknesses. This study also seeks to propose specific recommendations to make the program useful and relevant to the fast-changing conditions of the country. It seeks to focus on the objectives of teacher education, curriculum organization, teaching methods and techniques, student teaching, administration and supervision, and evaluation.